(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Emotionally expressive vocabulary is unique among linguistic universals, as it is it has all the expressive and impressive qualities. This allows her to act as the dominant means of language. In this article we noted: emotionally expressive vocabulary has great linguistic potency, it is capable of semantic and stylistic transposition. This is a vocabulary of style, its specificity is a kind of system organization created within the stylistic needs, in certain styles. Emotionally expressive vocabulary helps to reveal the stylistic features. "It lexical analysis on the" functions "is specific in every style", - as noted by G.J. Solganik. Emotional and expressive qualities of vocabulary may change: strengthen, weaken or disappear, or to acquire new connotations are updated, as can be divided according to the classification used in the work. We want to point out the need to distinguish between expressive and emotional elements in the language because it is dictated by the fact that functional tasks are different, in spite of their relationship.